Review of Metabolic Surgery for Type 2 Diabetes in Patients with a BMI < 35 kg/m2 - Hideharu Shimizu; Poochong Timratana; Philip R. Schauer; Tomasz Rogula (Journal of Obesity)
Bariatric/metabolic surgery is considered an accepted treatment option for type 2 diabetes mellitus (T2DM) with body mass index (BMI)  ≧  35 kg/m2. Mounting evidence also shows that metabolic surgery is effective for T2DM with BMI  <  35 kg/m2. To evaluate current status of metabolic surgery, we reviewed the available clinical studies which described surgical treatment for T2DM with mean BMI  <  35 kg/m2. 18 studies with 477 patients were identified. 30% of the patients was insulin users. The follow-up period ranged from 6 to 216 months. The weight loss effect was reasonable, not excessive. Mean BMI decreased from 30.4 to 24.8 kg/m2. Remission of T2DM was achieved in 64.7% of the patients with fasting plasma glucose and glycated hemoglobin approaching slightly above normal range. Clinical T2DM status was an important factor when selecting the eligible candidates for metabolic surgery. Postoperative complication rate of 10.3% with mortality of 0% in the studies has been acceptable. Even though it would be premature at this point to state that metabolic surgery is an accepted treatment option for T2DM with BMI < 35 kg/m2, it is clear that a high proportion of T2DM patients will derive substantial benefit from metabolic surgery.